Beyond the Movie Theater Sites, Sponsors, Uses, Audiences - Waller, Gregory A. (University of California Press, 2023)
Beyond the Movie Theater excavates the history of non-theatrical cinema before 1920, exploring how moving pictures were used in ways distinct from theatrical cinema. Looking away from the glimmer of the theater screen and stepping outside the light of the marquee, Beyond the Movie Theater reveals that sponsored moving pictures were put to a variety of uses and screened at a host of sites, targeting a surprisingly wide range of audiences. Relying on contemporary print sources and ephemera, Gregory A. Waller charts a heterogeneous, fragmentary, and rich field that cannot be explained in terms of a master narrative concerning origin or institutionalization, progress or decline. Uncovering how and where films were put to use beyond the movie theater, this book complicates and expands our understanding of the history of American cinema, underscoring the myriad roles and everyday presence of moving pictures during the early twentieth century. "A monumental triumph. Gregory A. Waller mines untapped historical evidence, revealing a vast and previously obscured area of early twentieth- century cultural activity. This is a fresh, surprising, and highly original contribution to American film history." - HAIDEE WASSON, author of Everyday Movies: Portable Film Projectors and the Transformation of American Culture "Outstanding. Waller brings a mastery of archival source work and careful methodological consideration to myriad contemporary periodicals and newspapers-many of which have been overlooked by previous historians of American cinema, until now." - PATRICK VONDERAU, University of Halle